Avanços e desafios na higienização das mãos na pandemia de COVID-19: uma revisão sistemática integrativa - Marinho, Camila Morilla Lemes (2022)
The objective of this research was to carry out an integrative systematic review on the advances and challenges of hand hygiene (HH) during the COVID 19 pandemic. Health professionals must adhere to “My five moments for HH”, as recommended by the World Health Organization - WHO. However, low levels of HM compliance are still a constant challenge. The Multimodal Strategy, proposed by the WHO, through the Global Challenge – “Clean care is safe care”, directs actions that contribute to adherence to HH. Method: This is an integrative systematic review, applying the research strategy in Medline, Embase and the Virtual Health Library – VHL. Results: The main challenges encountered in cleaning were: misinformation, inadequate infrastructure, difficult access and lack of alcoholic preparation. As for advances, we highlight the use of observation of HM electronically, the need for permanent and continuing education encouraging HM and using informative folders and posters close to the patient and HM sites, educating health professionals through feedback of the indicators raised during the observation period, to observe, understand and work on the individual behavior of the professional and adherence to HH according to examples of living with professionals who have good adherence to HH practice and technique